Regeneration of plants from protoplasts of Musa species (banana) - Panis, Bartholomeus; Sagi, L.; Swennen, Rony L. (1994)
Bananas are monocots and members of the genus Musa, family Musaceae. They are the second largest fruit crop in the world with an annual production of about 65 million tons (INIBAP 1993). The export trade, involving just dessert bananas of the Cavendish subgroup, comprises only 10% of the total banana production. Ninety percent is locally consumed and grown in backyards and small fields. Triploids are more widely cultivated than diploids and tetraploid